2021
DOI: 10.1002/ijfe.2502
|View full text |Cite
|
Sign up to set email alerts
|

Stock returns and interest rate differential in high and low interest rate environments

Abstract: In this study, we contribute to the literature in three ways. First, we test whether the response of stock returns to interest rate differential contrasts between high and low interest rate environments. Second, we further test whether positive and negative interest rate differentials impact differently on stock returns. For completeness, we examine the role of negative interest rate policy in the nexus by testing whether the response of stock returns to interest rate differential varies between negative and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…This shows that how the institutional climate has evolved from one characterized by managed credit rationing to a more competitive environment. Salisu and Sikiru (2021) explored the impact of interest rate differences on stock returns in both low-and high-rate conditions. The study indicated that, in negative interest rate environments, interest rate differentials have a more positive impact on stock returns in the short term than in positive interest rate environments.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that how the institutional climate has evolved from one characterized by managed credit rationing to a more competitive environment. Salisu and Sikiru (2021) explored the impact of interest rate differences on stock returns in both low-and high-rate conditions. The study indicated that, in negative interest rate environments, interest rate differentials have a more positive impact on stock returns in the short term than in positive interest rate environments.…”
Section: Introductionmentioning
confidence: 99%